Electrical and optical properties of reduced graphene oxide thin film deposited onto polyethylene terephthalate by spin coating technique - Rivera Tito, Harry Anderson; Beck, Sebastian; Romero-Nieto, Carlos (Applied optics, 2017)
We present the reduction of solution processed graphene oxide films by hydrogen iodide vapor. The films were studied by Raman spectroscopy and Fourier-transform infrared spectroscopy and its optoelectronic properties characterized. We obtained reduced graphene oxide films on polyethylene terephthalate flexible substrates with good electrical properties, 3.74×10−6 Ω·m, and high optical transmittance of 70% in the visible range. The fabricated layers contain graphene sheets with sizes up to ∼10 μm long and ∼6 μm wide. The presented solution, with highly concentrated processed graphene oxide, could be used as printing ink for manufacturing transparent and conductive electrodes on plastic substrates without the requirement of elevated temperatures.